A "Non-Invasive" Technique for Qualifying the Reinforced Concrete Structure. (27th September 2012) - Guida, Antonella; Pagliuca, Antonello; Tranquillino Minerva, Alessandro
Abstract : In recent years, a lot of studies on built heritage emphasize the need to use appropriate techniques to evaluate the current condition of the structure before designing an intervention. The research focuses on the restoration of reinforced concrete buildings that begin to show signs of decay and deterioration. To verify the state of a building, it's possible to use the "destructive" methods (that require a local removal of material) and "nondestructive" tests. The combined results from different "nondestructive" tests are very interesting instruments to assess the concrete strength. This methodological approach can help to reduce the possible errors when using the sclerometer and ultrasonic tests separately; in this way, the combined method called "SonReb" (SONic + REBound) was developed. This paper would highlight the importance with respect to cultural heritage buildings and on the studied structure and contribute to developed engineering strategies to maintenance and restoration. The above-defined methodology has been tested on a postwar building which is located in Gravina in Puglia (Italy): the "Centrone" theatre; it was built using a mixed structure, that is, reinforced concrete and bearing masonry built of local stone. The building was used until the 1990s and now is abandoned. The analysis and qualification of the masonry structures of built heritage show how this approach is useful for classifying the pathological events on each building and to implement the innovative solutions to improve the durability of a restoration intervention.